Goal! - Jefferies, Mike; Barrelle, Matt; Hoffman, Mark; Cannon, Danny (California : Buena Vista Home Entertainment, 2005)
Like millions of kids around the world, Santiago harbors the dream of being a professional footballer. However, living in the Barrios section of Los Angeles, he thinks it is only that--a dream. Until one day an extraordinary turn of events has him trying out for Premiership club Newcastle United
Executive producer, Lawrence Bender, Peter Hargitay ; co-producer, Jo-Burn...[et al.] ; film editing by Chris Dickens
Cast: Kuno Becker, Jorge Cervera, Herman Chavas, Alfredo Rodríguez, Donald Li, Kate Tomlinson, Jake Johnson, Zachary Johnson, Stephen Dillane, Sean Pertwee, Jonathan Hernandez, Alessandro Nivola
DVD Format
Dolby digital
In English, Thai, Spanish or Portuguese in optional English, Chinese, Indonesian, Thai, Malay, Korean, Spanish or Portuguese subtitles
Keywords: Soccer -- Drama; Soccer players -- Drama